Robustness Analysis For PID Controller Optimized Using PFPSO For Underactuated Gantry Crane System - Syed Hussien, Sharifah Yuslinda; Ghazali, Rozaimi; Jaafar, Hazriq Izzuan; Chong, Chee Soon (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
Gantry Crane System is widely used for material transportation. In this system, uncontrolled oscillation always be found during the moving process. This problem may extend the carrying time and cause safety problem. In this paper, it presents a method for controlling a Gantry Crane System based on Proportional-Integral-Derivative (PID) controller strategy. A combination of the Priority Fitness Scheme and Particle Swarm Optimization (PFPSO) is used to optimize the parameters of PID and PD controller (KP, KI, KD, KPS and KDS). A disturbance rejection control technique in which PID controller is employed to control accurately and robustly the trolley along a desired position with the minimize payload oscillation. Results from the simulation study clearly show that PID controller is a robust controller as a disturbance rejection and able to move the trolley to a desired position with minimize payload oscillation.